KITAB MANAQIB SYEKH ABDUL QADIR AL-JAILANI Resume Buku - Hakim, Ajid; Nurcahya, Yan; Syah, M Kautsar Thariq; Sugiarto, Deri; Hambaliana, Dandie; Noor, Arba'iyah Mohd (UIN Sunan Gunung Djati Bandung, 2025)
The Book of Manaqib of Sheikh Abdul Qadir Al-Jailani, published in 2011, by Ajid Thohir, offers a significant contribution to the study of Sufi historiography by illuminating a genre that is often neglected in Islamic historical scholarship. Focusing on the hagiographic narratives surrounding Sheikh Abdul Qadir Al-Jailani—a central figure in the Qadiriyya Sufi order—the book systematically examines the various versions and traditions of Manaqib literature, highlighting their role in shaping religious identities and spiritual practices among Muslim communities, particularly followers of the Qadiriyya-Naqshabandiyya orders. Using historical research methods, the study analyzes the structure, authorship, and epistemological foundations of several key Manaqib texts, arguing that these works are not only important sources for understanding the development of Islamic historiography but also serve to strengthen communal ties within the fiqh and Sufi traditions. The book shows how the Book of Manaqib functions as more than a record of miraculous deeds and virtues; It is an influential vehicle for spreading Islamic values, fostering piety, and cultivating collective memory in various Muslim societies.